Bridging the Gap between Business Practice and Data Science Approaches - Wang, Jiangping (Transactions on Engineering and Computing Sciences, 2025)
In data science and analytics, the driving force is not on how to perform analytics tasks or how to use advanced technology in analytics projects. Business problems and goals should always drive the overall approaches. Projects and applications in data science and analytics should serve business goals and help business decision making. In this paper, a case study that serves various directions in answering business questions is presented.